2005
DOI: 10.1093/alcalc/agh162
|View full text |Cite
|
Sign up to set email alerts
|

ERYTHROCYTE THIAMINE (Th) ESTERS: A MAJOR FACTOR OF THE ALCOHOL WITHDRAWAL SYNDROME OR A CANDIDATE MARKER FOR ALCOHOLISM ITSELF?

Abstract: No association was found between AWS severity and Th and its esters, while the diagnostic power of thiamine diphosphate (TDP) and Th was very high. TDP was the most significant among the parameters under study, confirming that erythrocyte TDP is a suitable marker of alcoholism: TDP sensitivity across subjects was 84.1%, specificity 85.4%, positive predictive value 82.4%, and negative predictive value 88.0%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…TDP is regarded as the physiologically active form of thiamine. Studies conducted in AL before the administration of vitamin supplements have shown that TMP [ 17 ] and TDP [ 18 ] concentrations are lower in patients than in healthy controls, whereas thiamine T concentration is abnormally high in some patients [ 17 ]. Thiamine metabolism, expressed as the ratio of phosphorylated to unphosphorylated thiamine, is also lower in AL patients [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…TDP is regarded as the physiologically active form of thiamine. Studies conducted in AL before the administration of vitamin supplements have shown that TMP [ 17 ] and TDP [ 18 ] concentrations are lower in patients than in healthy controls, whereas thiamine T concentration is abnormally high in some patients [ 17 ]. Thiamine metabolism, expressed as the ratio of phosphorylated to unphosphorylated thiamine, is also lower in AL patients [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Whole blood TDP concentration in the range of 90–220 nmol/L, TMP 1–10 nmol/L, TTP 1–13 nmol/L and free thiamin 2–15 nmol/L have been reported (Warnock et al., ; Lu and Frank, ; Gangolf et al., ). Lower total thiamin concentrations have been reported in whole blood of beriberi patients (Kawai et al., ; Kuriyama et al., ) and in erythrocytes of alcoholic subjects (Mancinelli et al., ; Ceccanti et al., ), compared to healthy individuals. In a longitudinal study in which four young adults were maintained on a constant diet for 60 days (1.55 mg thiamin/day), within‐subject variation in whole blood total thiamin concentration in the order of 8–10% was reported (van Dokkum et al., ).…”
Section: Definition/categorymentioning
confidence: 92%
“…All patients had intakes of vitamin E and folate below UK recommended standards, while 85-95% of patients had low intakes of selenium and Vitamin D. Between 50% and 85% of all patients had intakes of calcium, zinc, Vitamins A, B(1), B(2), B(6) and C below UK recommended standards in (Manari et al, 2003). Furthermore, several studies showed that 30-80% of alcoholics become thiamine deficient because of poor diet, impaired absorption, vomiting, and direct inhibition of the pyrophosphokinase (Butterworth et al, 1993;Ceccanti et al, 2005;Heap et al, 2002;Homewood et al, 1997;Kopelman, 1995;Lieber, 2003). Ba et al (1999) analysed the combined effects on newborns of a thiamine-deficient diet and alcohol exposure in pregnant and lactating rats.…”
Section: The Combined Effects Of Malnutrition and Alcohol Misusementioning
confidence: 99%